Progressive new world : how settler colonialism and Transpacific exchange shaped American reform - Lake, Marilyn (Harvard University Press, 2019)
In Progressive New World, Marilyn Lake seeks to explain the paradoxes of Progressive reform in the United States and Australia in the late nineteenth and early twentieth centuries, when democratic practices such as women's and workers' rights, children's welfare, and indigenous assimilation existed alongside racial segregation and oppression of indigenous peoples. Lake demonstrates the critical importance of settler colonialism and its attitudes toward native inhabitants in forming white settlers' mindsets of racial solidarity in both American and Australian societies. Progressive New World suggests that the very idea of "progressivism" rested on temporal distinctions between Old World (feudal and monarchic) and New World (democratic) societies and concomitant racialized distinctions between settlers and indigenous peoples-deemed either "advanced" or "backward," "civilized" or "primitive," in a framework that cast the past as inherently oppressive and the future as a place of inevitable evolutionary advancement. Lake demonstrates the force of progressive thinking, but also its limits.--